2022
DOI: 10.3390/jcm11113019
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions after Carotid Artery Stenting—1-Year Follow-Up Study

Abstract: Background: The revascularization of carotid arteries minimizes the risk of future cerebral stroke and usually improves cognitive functions. The aim of this study was to assess changes in cognitive function and verify the hypothesis assuming an improvement of selected cognitive functions—psychomotor speed, visuospatial episodic memory, executive function and verbal fluency—in patients after carotid artery stenting during a 12-month follow-up. Methods: 47 persons subject to CAS, including 13 symptomatic persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The results of a previously published study showed improvements in the following cognitive functions: psychomotor speed, visuospatial episodic memory and executive function in patients 1 year after CAS. Importantly, we failed to observe a decline in any of the analyzed cognitive abilities after CAS at 1-year follow-up ( 23 ). Similar conclusions are also reached by other researchers ( 24 31 ), who take the position that carotid artery stenting improves cognitive functioning in both basic and more complex cognitive functions in people with carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 90%
“…The results of a previously published study showed improvements in the following cognitive functions: psychomotor speed, visuospatial episodic memory and executive function in patients 1 year after CAS. Importantly, we failed to observe a decline in any of the analyzed cognitive abilities after CAS at 1-year follow-up ( 23 ). Similar conclusions are also reached by other researchers ( 24 31 ), who take the position that carotid artery stenting improves cognitive functioning in both basic and more complex cognitive functions in people with carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 90%
“…Studies show that the benefit of CAS does not only rely on reducing the risk of stroke, it also improves the cognitive function of the brain, as shown in Figure 3 [ 86 , 87 ]. In a study including 47 patients to assess the psychomotor speed, visuospatial episodic memory, executive function, and verbal fluency of patients, all of the aspects except verbal fluency have shown improvement [ 88 ]. Furthermore, in a study including 31 patients, the patients showed improvements in attention, memory, visuospatial, and language.…”
Section: Reviewmentioning
confidence: 99%